O desenho das habitações populares e sua influência sobre a privacidade e conflitos de convivência dos moradores: casos dos residenciais Tocantins 1 e 2 - Pereira, Talita Rodrigues (2017)
The construction of housing developments of social interest has been carried out throughout Brazil without much reflection on how "the repetition of housing types" can meet the culture, the family arrangement or the needs of quite different lives. Thus, post-occupation evaluation (POE) has been widely discussed in Brazil as a means of promoting technical and theoretical argumentation, using methodological tools to qualify buildings, not only on technical aspects, but also on the user. In this sense, the hypothesis is that the decrease of free and built spaces negatively affects the quality of privacy and the quality of social interactions in housing developments of vertical multifamily social interest (HIS-mv). To do so, this research aims to identify and analyze, through the study of the Tocantins Residences 1 and 2, located in the city of Uberlândia-MG, the circumstances in which the design of the built environment affects the privacy of its residents. To present this study, the research is structured methodologically in four approaches: i) multidisciplinary discussion about the concept of privacy; (ii) characterization and contextualization of the object of study and its residents; (iii) the methodology used in the research; (iv) the application and results of POE instruments (technical analysis on graphic pieces, walkthroughs, questionnaires and interviews) used to evaluate the quality of intra- and extra-residential privacy; (vi) the final considerations and their refutations of findings on recommendations for new HIS-mv. The results of the research showed that the quality of the privacy in the home is more strongly related to the degree of intimacy among its residents, than to the design of the dwelling, while the quality of the privacy of the home is related to the lack of spaces for the collective recreation and the appropriation of residual elements of construction, which in turn, becomes a facilitator for the emergence of conflicts of coexistence. Finally, this research advances in the field of POE, on the methodological procedures to evaluate the quality of privacy in HIS and brings new design parameters to be considered in future housing developments of vertical social interest, in order to improve the quality of privacy as well as improving social relations with the new neighborhood.